2018
DOI: 10.1021/acs.orglett.7b03500
|View full text |Cite
|
Sign up to set email alerts
|

Synthetic Studies toward the Tetrapetalones: Diastereoselective Construction of a Putative Intermediate

Abstract: A strategy toward tetrapetalones was explored including a site-selective ethylenation of the silyl enol ether A to afford a quaternary stereocenter that serves in a stereogenic capacity. Regio- and diastereoselective reactions were observed in conjunction with the oxidative formation of cation B, which included subsequent selective formation of either carbon-oxygen or carbon-carbon bonds at the δ or ζ position on the seven-membered ring. The fourth ring was formed using a Stetter reaction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 35 publications
0
6
0
Order By: Relevance
“…The second approach for the construction of the C14–C6 bond used a Stetter reaction catalyzed by the N-heterocyclic carbene (NHC) from precatalyst 17 developed by Rovis. The NHC from precatalyst 17 can be used for diastereoselective intramolecular reactions, such as the benzoin reaction with aliphatic aldehydes, , and the Stetter reaction where it was employed by Pettus and Bai in their work toward the tetrapetalones . Because of the ease with which the aldehyde mixture containing 14a and 14b could be prepared from crude extracts of E.…”
Section: Resultsmentioning
confidence: 99%
“…The second approach for the construction of the C14–C6 bond used a Stetter reaction catalyzed by the N-heterocyclic carbene (NHC) from precatalyst 17 developed by Rovis. The NHC from precatalyst 17 can be used for diastereoselective intramolecular reactions, such as the benzoin reaction with aliphatic aldehydes, , and the Stetter reaction where it was employed by Pettus and Bai in their work toward the tetrapetalones . Because of the ease with which the aldehyde mixture containing 14a and 14b could be prepared from crude extracts of E.…”
Section: Resultsmentioning
confidence: 99%
“…These natural products present a unique fused tetracyclic core that contains a tetramic acid, a para -quinol, and four contiguous stereogenic centers. At the time of our studies, synthetic approaches had been disclosed by Porco, Sarpong, Hong, and Pettus, but no synthesis of the tetracyclic core had been achieved. Several years after our report, tetrapetalone A was finally conquered in an elegant synthesis by the Wood group .…”
Section: Total Synthesis Of Tetrapetalone A–me Aglyconmentioning
confidence: 99%
“…consulted Prof. Tom Pettus, world expert on methods for dearomatization of phenol derivatives . He suggested that we use fairly exotic Rh/tBuOOH oxidation conditions, first disclosed by Doyle. , As predicted, the protocol is effective in the tetrapetalone context, giving the para - tert -butylperoxide 85 in 84% yield. However, our trials were not yet over.…”
Section: Total Synthesis Of Tetrapetalone A–me Aglyconmentioning
confidence: 99%
“…The latter after two steps gave 265 which possessed the tetracyclic core of tetrapetalones (Scheme 63). [126] …”
Section: Application Of Stetter Reaction In Total Synthesis Of Naturamentioning
confidence: 99%
“…[125] The latter after two steps gave 265 which possessed the tetracyclic core of tetrapetalones (Scheme 63). [126] Curcusone C 275, a diterpenoid extracted from the root barks of Jatropha curcas, Jatropha curcas L. (Euphorbiaceae) is a drought-resistant shrub obtained from South and Central America. [127] Moreover, extracts from J. curcas have been extensively examined for their secondary metabolite content.…”
Section: Hirota and Co-workers In 2003 Isolated Tetrapetalones Frommentioning
confidence: 99%